Analisis Efektivitas UU P2SK Dalam Memitigasi Risiko Sistemik di Indonesia - Siti Nuranisya; Atang Abdul Hakim (SPT. haria Journal and Education Center Publishing, 2026)
Law Number 4 of 2023 on the Development and Strengthening of the Financial Sector (P2SK Law) serves as a legal response to regulatory fragmentation and the complexity of risks within Indonesia's financial sector. This study aims to analyze the effectiveness of the P2SK Law in mitigating systemic risk using a normative juridical approach. The analysis indicates that the omnibus law method employed in the P2SK Law has successfully integrated previously fragmented legal frameworks and strengthened institutional coordination among Bank Indonesia, the OJK, and the LPS under the Financial System Stability Committee (KSSK). Although the P2SK Law provides a robust legal basis for supervising financial technology innovation and consumer protection, its long-term effectiveness faces implementation challenges, including delays in issuing derivative regulations, potential sectoral ego, and infrastructure capacity gaps in microfinance institutions. This study concludes that while the P2SK Law is a strategic step toward fortifying the financial system stability architecture, its success heavily depends on the consistency of law enforcement and inter-institutional policy synchronization.